Paradigm Shift in Orthopedic Residency Training in Times of Covid-19 Pandemic: Experience of an Indian Teaching Institute - Vivek Singh; Varun Garg; Sunny Chaudhary; Roop Bhushan Kalia; Pradeep Meena; Mohit Dhingra; Pankaj Khandwal; Shobha S Arora (Asian Journal of Medical Research, 2021)
Background: The resident training program took a backseat during the covid-19 crisis. This paper describes new ways and strategies of ortho- pedic resident training and conducting exit exams during this pandemic. Subjects and Methods: A retrospective observational study was done in the department of orthopedics over a period of two months during the pandemic at a teaching level hospital in India where orthopedic and non-orthopedic work and academic activities attended by the residents were compared from the data from the preceding two months of the crisis. Various means of conducting the summative exams were also analyzed. A p- value< 0.05 was found to be statically significant. Results: Out  of 34 residents, thirty-three residents were present in the department along with 12 fellows and three senior residents. Residents were divided into three teams to provide COVID and emergency services. All elective operations and routine out-patient department services were suspended during the pandemic. 27 major orthopedic operations and 38 academic activities were carried out. No significant correlation was found in the academic activities and attendance of the residents during the pandemic and preceding period. The exit exams were also conducted in a novel way with the help of a digital platform. Conclusion: The resident training was compensated by interactive sessions on digital platforms.